The Postcolonial Unconscious in North African Migrant Fiction - ALI, Imad OILAD (International Journal of Language and Literary Studies, 2024)
The impact of the postcolonial unconscious on North African migrant fiction has been extensively explored and revealed through both theoretical frameworks and literary practices throughout the postcolonial era. Scholars and writers alike have delved into how the psychological remnants of colonialism continue to influence the narratives, themes, and character development in this body of work. This ongoing examination highlights the deep-seated cultural and psychological legacies that shape the identities and experiences of both individuals and communities within North African migrant literature. As a reflection of the long-lasting consequences of colonial history on people and society, North African migrant writers, like other postcolonial writers worldwide, tackle themes of identity, displacement, and post-colonialism. Theorists like Sigmund Freud, Jacques Lacan, Frantz Fanon, and Jacques Derrida have theorized that the unconscious influences language and subject creation, which in turn shapes their narratives. This analysis uses Fanon’s concept of the postcolonial unconscious, which explores the psychological effects of colonialism, such as internalized trauma and cultural hybridity, as a major framework. This study examines how postcolonial unconscious and related themes appear in the writing of North African writers who have immigrated to Europe and the USA, emphasizing the psychological and cultural effects of colonization on both individuals and groups. In addition to offering in-depth examinations of some texts, the paper presents a comprehensive view of the importance of postcolonial literary criticism in comprehending the complexities of postcolonial societies.